Foreign Trade Relations of the Visegrad Group: the Transformation of the Role of the Russian Federation - A. S. Chetverikova (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2019)
The article analyzes changes in the foreign trade sector of the Visegrad countries after their entry to the European Union with special focus on relations with Russia. The territorial orientation of trade relations of Hungary, Poland, Slovakia and the Czech Republic is considered. The author highlights the continuing trend of the EU’s market priority for the Visegrad group against the background of strengthening the role of partner countries of “four” and the Asian vector. Special attention is paid to the sectoral structure of foreign trade of the Visegrad countries and its transformation since 2003. The Russian Federation’s role in foreign trade of Hungary, Poland, Slovakia and the Czech Republic is analyzed not only in terms of the priority of the Russian direction, but also the possibilities of changing existing positions. The dynamics of the Russian positions in foreign trade sectors of four Viseg-rad countries are considered highlighting the main factors influencing trade relations. In this regard, the changed in 2014 political and economic conditions of mutual trade including the factor of sanctions are analyzed in detail. The sectoral structure of trade relations with Russia allows to say that there are remaining imbalances and it’s atypical for the Visegrad countries. The Russian positions in the foreign trade of the Visegrad countries at present time are estimated as weakened, corresponding to the period of the early 2000s which are a consequence of the influence of one of the long-term and negative factors in recent years while the trade structure maintains relatively stable. The existing dynamics of recovery of trade relations between Russia and Hungary, Poland, Slovakia and the Czech Republic suggests that reaching the pre-crisis level will not happen in the near future.